River‐of‐origin assignment of migratory Striped Bass, with implications for mixed‐stock analysis. Issue 1 (22nd December 2022) - Wojtusik, Kristopher J.; Berlinsky, David L.; Kenter, Linas W.; Kovach, Adrienne I.
Abstract: Objective: The Striped Bass Morone saxatilis is an anadromous teleost with a native range extending north from the Gulf of Mexico into Canadian waters. Far‐ranging coastal migrations support one of the most popular recreational fisheries in the United States. Identifying the underlying population genetic structure of the spawning populations and the genetic markers capable of differentiating among them advances our understanding of these economically and ecologically important fish and enables more targeted management to occur. Methods: We used a restriction site‐associated DNA sequencing approach to identify neutral and adaptive single‐nucleotide polymorphisms (SNPs), and we determined the population genetic structure of 438 adult Striped Bass sampled from nine spawning locations along the Atlantic coast from the Roanoke River, United States, to the Miramichi River, Canada. Result: The two Canadian populations (Shubenacadie and Miramichi rivers) were genetically distinct from U.S. populations and from each other. Neutral loci differentiated Striped Bass from U.S. waters into four genetically distinct populations: Roanoke River, Hudson–Kennebec River, Upper Chesapeake Bay–Potomac River–Delaware River, and Choptank River (eastern Chesapeake Bay). Outlier loci further differentiated the Delaware River from the Chesapeake Bay tributaries, suggesting that there may be local adaptation in the face of gene flow. We identified 1300 highly informative SNPs (the top 10% [with respect to the genetic differentiation index F ST ] of the full suite of 13, 361 SNPs in our study) capable of assigning fish with at least 90% accuracy to their river of origin; through simulations, we established their applicability for conducting robust mixed‐stock analyses of the coastal migratory Striped Bass fishery. Conclusion: This study demonstrated that neutral and adaptive loci together provide evidence for fine‐scale population structure of migratory Striped Bass, and these loci provide the most informative genetic panel for mixed‐stock analysis of Striped Bass to date, capable of assigning fish to their spawning river of origin. Impact Statement: Migratory Striped Bass that occur along the Atlantic coast of the USA and Canada are structured into genetically distinct populations, corresponding to their spawning river of origin. We identified a suite of genetic markers that will enable fishery managers to determine the stock composition of the mixed coastal Striped Bass fishery.